EXTRACTION OF LIPIDS FROM MUNICIPAL SEWAGE SLUDGE FOR PRODUCTION OF BIODIESEL VIA TRANSESTERIFICATION PROCESS - BHARATHI.P,; KARTHIGA.R,; SHAMLI.M,; VIVETHA.K,; SUBATHRA.M, (International Journal of Pharma and Bio Sciences, 2014)
Biodiesel also called as fatty acid methyl esters (FAME) has become more attractive because of its environmental benefits. Biodiesel is the most promising renewable, biodegradable, alternative fuel is produced from various lipids sources. Here the municipal secondary sewage sludge is taken as potential sources of lipids. The potential of using sludge from municipal waste water treatment plant as feedstock for lipid is investigated because of disposal problems occurring due to increase of urbanization and industrialization. The secondary or activated sludge composed of suspended solids and microbial cells containing phospholipids produced during aerobic biological treatment. In this study, analyses were done on lipid extraction and biodiesel production from dried secondary sludge. A maximum of lipids was extracted using hexane and methanol as solvent from secondary sludge. FAME is obtained from triglycerides by acid – catalyzed transesterification using sulfuric acid. Once the biodiesel is produced it is analyzed by gas chromatography – mass spectrometry(GC-MS). GC-MS method is used for determination of fatty acid, esters,alcohol, mono,di,tri glycerides obtained. The analysis of FAME revealed fatty acids composition with predominance of palmitic acid, steric acid, oleic acid and linoleic acid.